Screening of Antistress Properties of Herbal Extracts and Adaptogenic Agents – A Review - D. M, Kannur; A.A, Kulkarni; M.P, Paranjpe; M.V, Navangul (Pharmacognosy Reviews)
Stress is a daily phenomenon faced by every human, normal functioning of every individual is dependent on optimum levels of stress; it is very vital that stress is kept under control and normal functioning is not hampered due to excess of stress. Adaptogens are such herbal agents, which help the body to overcome excess stress even in chronic cases. Many marketed formulations claim to possess antistress actions, but still many herbs which have claims to be general tonics as well as wonder drugs need to be investigated and there claims be authenticated. In recent era there is a great thrust on screening of herbal extracts and formulations for Adaptogenic action. In this article efforts have been taken to list as well as discuss various models and parameters used for antistress activity. The motto is to discuss the models, to bring them under one title, which would surely prove to be some help to the researchers.
Keywords: Adaptogens; Antistress; Physical endurance